Epidemiological study of gonorrhea - Sopungco, Herminda O. A.
An epidemiological study on the commonly called "the clap", "gleet" or the "drip", a gonorrhea caused by the gonococus. As a common venereal diseases, its control was cited as one of the major problems in medical practice, since it occurs 10 or more times as frequently as syphilis.
Thesis (MS Public Health) -- University of the Philippines Manila
Keywords: Gonorrhea--Epidemiology.